Análise do perfil de pessoas idosas após Covid-19 e perspectivasdo cuidado: um estudo realizado no Hospital Universitário de Santa Maria - Lima, Graziele Pires (2022)
The present study aimed to outline the profile of elderly patients after hospital dischargedueto COVID-19 and to map the perspectives of professionals regarding care at the UniversityHospital of Santa Maria. Quali-quantitative, descriptive, retrospective research. 290electronicmedical records of patients aged 60 or older, with a positive diagnosis of COVID-19, wereanalyzed. With health professionals from the care units for patients with COVID-19: intensivecare unit, outpatient clinic, and home care, a focus group was carried out. Regardingtheprofile of the patients, there was a predominance of males, married with incompleteprimaryschool, with associated comorbidities at the time of hospitalization, with an emphasisonsystemic arterial hypertension. As for the profession and the use of immunizers for COVID-19, there was a gap in the recording of this information, which is assumed not tohavebeencollected and/or transcribed into the electronic medical record, signaling actions intheinstitution that seek awareness of the importance of feeding the systemwith completepatientdata, as required by law. As for risk behavior for smoking and alcoholism, it was identifiedthat most of the medical records contained low consumption information for thesedrugs.Regarding the perception of professionals about the prognosis of patients with COVID-19, itis an unknown issue to be monitored in the long term, as there are issues of balanceandhearing loss due to ototoxic antibiotics, swallowing problems that can lead to drowningduetoliquid consistency, leading to recurrent pneumonia, vocal alterations for a long timewithanendotracheal tube or tracheostomy, hypotony, joint bone wear, tachycardia, risk of thrombosis,pulmonary complications, in addition to the emotional and social impacts, whichconstituterecurrent sequelae and that need to be accompanied by an interdisciplinary team. Thepresentstudy identifies a public of elderly people with fragilities mitigated by COVID-19, associatedwith previous comorbidities, which potentiated the worsening of the disease, as well asitsprognosis, demanding longitudinal multidisciplinary assistance fromhealth professionals,guided by educational actions in health that add values to the context of eachindividual,as well as their caregivers.